ENHANCING SELF-DIRECTED LEARNING IN ARABIC SPEAKING COMPETENCY THROUGH DORATOON AND GOOGLE SITES - Nurul Hidayah; Mukmin Mukmin; Nabila Nurul Aini; Febri Yansyah; Nur Khamimi Zainuddin (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2026)
One of the main challenges in teaching maharah kalam, or Arabic speaking skills, is the lack of real opportunities for meaningful oral interaction. Traditional, teacher-centred methods are still widely used, which often limits students’ ability to communicate confidently and independently. This study set out to explore how integrating Self-Directed Learning (SDL) with digital tools like Doratoon and Google Sites could help overcome these challenges. Using a combination of qualitative and quantitative approaches, the research gathered insights from classroom observations, interviews, and documentation, as well as pre- and post-tests involving 30 students. The results showed a noticeable shift from teacher-led instruction to a more student-centred and participative environment. Students’ average speaking scores improved significantly, rising from 57.33 to 91.33, with an N-Gain of 80.56%. These findings suggest that when technology is thoughtfully combined with SDL, it can create a more engaging, autonomous, and effective learning experience for students. Ultimately, this study offers a promising new model for making Arabic-speaking instruction more dynamic and centred on the learner.